Fun with foam, on my own: 58 fun & funky projects made with precut foam shapes - Hacker, Katie (Hot Off The Press Oregon, 2001)
Fun with Foam, On My Own: 58 Fun & Funky Projects Made with Precut Foam Shapes is a creative activity book that provides step-by-step instructions for making a variety of crafts using pre-cut foam shapes. Perfect for young children, this book encourages imagination and fine motor skills while offering hours of fun and entertainment.